Light and Dark Realm Phenomenon: Analysis of Persona and Shadow in Hermann Hesse’s Demian - Andi Putri Varellita; Margawati, Prayudias (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study analyzes psychological duality in Hermann Hesse's novel Demian through the lens of Jungian psychoanalytic theory, focusing on the concepts of persona and shadow in relation to the light and dark realms phenomenon. Employing qualitative textual analysis, this study delves into Sinclair's psychological development and self-integration as portrayed in the symbolic assertion between the dichotomy. Discussions and findings reveal that this dichotomy is not an absolute opposite but a highly dynamic reality that helps Sinclair get to know himself, the process of understanding himself in the chaotic event of psychological conflict. Sinclair’s contemplation of the sparrow hawk painting and his conversation with Demian and Pistorius serve as important moments in this internal turmoil. This research contributes to the fields of literature and psychology by presenting Demian's novel as a view that the light and dark realms are a highly dynamic phenomenon that influences the emergence of persona and shadow in a person. However, there are still limitations in contextualizing the novel's pre-World War I socio-historical influences. Future research could explore how historical tensions shaped Sinclair's journey, deepening the analysis of personal transformation within broader societal changes.